2016
DOI: 10.1016/j.ssresearch.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction, ethnicity and neighbourhoods: Is there an effect of neighbourhood ethnic composition on life satisfaction?

Abstract: Immigrants and ethnic minorities tend to have lower life satisfaction than majority populations. However, current understanding of the drivers of these gaps is limited. Using a rich, nationally representative data set with a large sample of ethnic minorities and matched neighbourhood characteristics, we test whether first and second generation minorities experience lower life satisfaction once accounting for compositional differences and whether, specifically, neighbourhood deprivation impacts their wellbeing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 68 publications
9
86
0
3
Order By: Relevance
“…While our finding of lower overall happiness scores in respondents from ethnic minorities is consistent with results of some more general surveys,14 our results (especially the lower levels of happiness these respondents expressed with support from clinical colleagues) merit reflection.…”
Section: Discussionsupporting
confidence: 90%
“…While our finding of lower overall happiness scores in respondents from ethnic minorities is consistent with results of some more general surveys,14 our results (especially the lower levels of happiness these respondents expressed with support from clinical colleagues) merit reflection.…”
Section: Discussionsupporting
confidence: 90%
“…Another explanation is that the relationship between education and life satisfaction varies across different institutional contexts. For example, using a similar set of control variables in a life satisfaction regression equation, the effect of having a college degree on life satisfaction is found to be positive and statistically significant in the UK (Knies et al, 2014) but negative and statistically significant in Australia (Shields et al, 2009). …”
Section: Conceptual Framework and Related Researchmentioning
confidence: 99%
“…The large literature on life satisfaction has analysed the impact of various individual and socio-economic characteristics and events, such as personality, gender, age, income, employment status (including the experience of unemployment), divorce, migration and so on (Diener et al 1999;Stutzer and Frey 2010). Recent studies analyse the impact of various macro-level and institutional factors such as environmental quality or neighbourhood deprivation (Ferrer-i-Carbonell and Gowdy 2007;Knies et al 2014;Morrison 2011;Shields et al 2009).…”
Section: The Utility Frameworkmentioning
confidence: 99%
“…Rather than diversity per se, also for minority groups what may affect life satisfaction may be the presence of people sharing the same 'culture'. The small number of observations prevents us from more in-depth analyses; however, recent research has shown that in most cases minority groups' life satisfaction is not affected by the presence of co-ethnics in the neighbourhood (Knies et al 2014). This result also supports the idea that after few years of residence in the UK immigrantsespecially those coming from countries that are very different than the UK -tend to feel British (Manning and Roy 2010), and that ethnic British people have higher levels of Britishness than white British people themselves (see Nandi and Platt (2014); see also Masella (2013) for cross-country evidence).…”
Section: Impact Of Diversity On Life Satisfactionmentioning
confidence: 99%